PERENCANAAN RUMAH PRODUKSI BAWANG MERAH DI KELURAHAN SRIGADING KABUPATEN BANTUL YOGYAKARTA - Vira Yulianti; Artita Devi Maharani; Eska Stefani (JURNAL ILMIAH AGRITAS, 2026)
This study aims to develop a business plan for a Shared Production House as part of the implementation of the Desa Preneur program to optimize shallot processing in Srigading Village, Kapanewon Sanden, Bantul Regency. The research was conducted from January 2025 to December 2025 using a qualitative descriptive approach with data collection techniques such as interviews, observation, documentation, and literature study. Data analysis used the Business Model Canvas (BMC) framework to map nine elements of the business model, namely customer segments, value propositions, distribution channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structure. The results and conclusions of the study show that the Joint Production House is still in the planning stage, so a focused operational strategy is needed to support the development of businesses based on local potential. The main challenges include limited production facilities, product legality, human resource capabilities, and suboptimal marketing strategies. However, there are great opportunities in the form of abundant raw materials, increasing consumption trends for fried onions, government support, digital marketing potential, and partnership opportunities with the business sector and certification agencies. In conclusion, the five-year revenue and operational cost projections show a positive growth trend, with revenue in the fifth year estimated to reach IDR 30,479,905,805. Therefore, structured material and cost planning is needed to ensure that the Joint Production House can operate efficiently, sustainably, and competitively.